2018
DOI: 10.4103/ejd.ejd_77_18
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of calcium hydroxide through dentinal tubules of retreated root canals: An in vitro study

Abstract: Objective:Studies about the dispersion of hydroxyl ions through dentin of endodontically retreated teeth are scarce. The present study aims at examining the diffusion of calcium hydroxide in vitro by recording the pH changes of retreated root canal using two types of calcium hydroxide preparations.Materials and Methods:A total of 45 recently extracted single-rooted mandibular first premolars were collected and cleaned from calculus and remains of periodontal tissue. The teeth so collected were stored in thymol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(23 reference statements)
1
9
1
Order By: Relevance
“…hence the number of appointments is reduced . According to the results obtained in our study RC Cal showed the Highest pH on the 7 th day (12.6) on 10 th day (10.15), 14 th day (9.8) and on 30 th day .Our results was in favour of the study conducted by punit et al who found that release of Hydroxyl ion was more for RC Cal in comparison to that of Calcium Hydroxide with Saline this is mainly attributed as there is sudden rise in the pH after 24 th hour on the other hand for RC Cal there is gradual increase in the pH with decrease in pH after 15 days to 30 th days 15 Metapex and Vitapex both are oil based formulation.They are formed from Calcium Hydroxide with Idoform with silicon oil. These type of oil based vehicles are said to be non water soluble hence promoting low solubility and diffusion within the tissue , such type of formulations may remain in the root canal for a longer time .Various oils are used for the formation of such types of vehicles they include Olive oil, Silicon oil, Camphor, Metayacresylacetate and some fatty acid such as Oleic ,Linoleic and Isostoaric acid.…”
Section: Result:-contrasting
confidence: 97%
“…hence the number of appointments is reduced . According to the results obtained in our study RC Cal showed the Highest pH on the 7 th day (12.6) on 10 th day (10.15), 14 th day (9.8) and on 30 th day .Our results was in favour of the study conducted by punit et al who found that release of Hydroxyl ion was more for RC Cal in comparison to that of Calcium Hydroxide with Saline this is mainly attributed as there is sudden rise in the pH after 24 th hour on the other hand for RC Cal there is gradual increase in the pH with decrease in pH after 15 days to 30 th days 15 Metapex and Vitapex both are oil based formulation.They are formed from Calcium Hydroxide with Idoform with silicon oil. These type of oil based vehicles are said to be non water soluble hence promoting low solubility and diffusion within the tissue , such type of formulations may remain in the root canal for a longer time .Various oils are used for the formation of such types of vehicles they include Olive oil, Silicon oil, Camphor, Metayacresylacetate and some fatty acid such as Oleic ,Linoleic and Isostoaric acid.…”
Section: Result:-contrasting
confidence: 97%
“…25 Therefore, the use of H 2 O 2 as an intracoronal bleaching agent decreased extraradicular pH all groups. This study suggests that was a pH change of the external medium, in agreement with the results of Rokaya et al, 25 de Sá et al, 26 and Lou et al 27 Cai et al 28 and Mustafa et al 29 found that the pH of the dentin increases after placing calcium hydroxide Ca(OH) 2 in the root canal. de Sá al.…”
Section: Discussionsupporting
confidence: 90%
“…Cai et al 28 and Mustafa et al 29 found that the pH of the dentin increases after placing calcium hydroxide Ca(OH) 2 in the root canal. de Sá al.…”
Section: Discussionmentioning
confidence: 99%
“…Hand files and rotary instruments accompanied by intermittent irrigation with sodium hypochlorite (NaOCl) and calcium hydroxide dressing is the traditional protocol used for the treatment of teeth with irreversible pulpitis and/or peri‐apical lesions 1‐4 . A precise classification that addressed root and canal anatomy together with root morphology was therefore warranted.…”
Section: Introductionmentioning
confidence: 99%